Development Of A River Water Quality Management Information System. - Belaton, B; Hj. Talib, A.Z.; Md Ismail, Ahmad Izani (2004)
Rivers provide water for domestic consumption, agriculture, industry and recreation. Thus, to ensrue consistent high quality, river water quality should be monitored on a regular and systematic basis.